2019
DOI: 10.1002/cam4.2468
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of five long noncoding RNAs expression as competing endogenous RNAs in regulating hepatoma carcinoma

Abstract: Liver cancer is the most common cancer and is the epitome of a recalcitrant cancer. Increasing evidence shown that long noncoding RNAs (lncRNA) were associated with cancer‐related death and could function as a competing endogenous RNA (ceRNA). To explore regulatory roles and potential prognostic biomarkers of lncRNA for liver cancer, RNA‐sequencing expression data were downloaded from the TCGA database and GEO database. A total of 357 patients were randomly divided into a discovery group and a validation group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Differentially expressed RNAs were screened from RNA-seq data and miRNA-seq data in TCGA () separately, since lncRNAs and mRNAs were included in the RNA-seq database and miRNAs were included in the miRNA-seq database (21). Then, the data of RNA expression in NSCLC were extracted from these two databases and normalized by ‘DESeq2’ and ‘edgeR’ package.…”
Section: Methodsmentioning
confidence: 99%
“…Differentially expressed RNAs were screened from RNA-seq data and miRNA-seq data in TCGA () separately, since lncRNAs and mRNAs were included in the RNA-seq database and miRNAs were included in the miRNA-seq database (21). Then, the data of RNA expression in NSCLC were extracted from these two databases and normalized by ‘DESeq2’ and ‘edgeR’ package.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in our ceRNA network, GAS6-AS1 and LRRC4 both interacted with miR182; thus, we predicted that GAS6-AS1 could bind miR182 and act as a ceRNA, therefore modulating the levels of the LRRC4 in KIRP. Using PubMed, we found that the only report on the function and mechanism of LINC00200, was from Lou et al (2019) . They reported that LINC00200 played a critical part in early stage hepatocellular carcinoma (HCC) after analyzing RNA-sequencing expression data of liver cancer from the TCGA and GEO database ( Lou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using PubMed, we found that the only report on the function and mechanism of LINC00200, was from Lou et al (2019) . They reported that LINC00200 played a critical part in early stage hepatocellular carcinoma (HCC) after analyzing RNA-sequencing expression data of liver cancer from the TCGA and GEO database ( Lou et al, 2019 ). In our study, high expression of LINC00200 was associated with poor survival outcomes in KIRP patients and higher expression of LINC00200 at later tumor stages, which indicated that LINC00200 may have been an oncogene in renal clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the existence of tumor-infiltrating immune cells, especially leukocytes, is also an essential evident witnesses of the activity of immune system and is supposed to play critical roles in cancer growth, progression and metastasis including the COAD ( Dadabayev et al, 2004 ; Halama et al, 2009 ; Palmqvist et al, 2013 ). However, there are only a few studies focusing on the regulatory mechanism between ceRNA networks and tumor-infiltrating immune cells, not containing COAD ( Lou et al, 2019 ; Yang et al, 2019 ; Zhao R. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%